THE EFFECT OF E-WOM, E-TRUST AND E-SERVICE QUALITY ISLAMIC ON PURCHASE DECISIONS ON MS GLOW SKINCARE PRODUCTS - Muhammad Nazri Wahdana; Imsar Imsar (Jurnal Ekonomi, 2022)
The purpose of this study was to examine the effect of the quality of E-WOM, E-Trust, and Islamic E-Service on purchasing decisions for MS Glow skin care products. The data source for this research is primary data obtained from the sample. In particular, primary data was obtained from residents of Medan who bought MS Glow skin care products at least once, including a sample of 100 respondents from various areas of Medan using the questionnaire distribution method. (1) The results of this study indicate that the E-WOM variable has a significant and positive effect on purchasing decisions. (2) The E-TRUST variable has a slightly significant positive influence on purchasing decisions. (3) the Islamic e-service quality variable has a partial and significant positive effect on purchasing decisions; (4) Simultaneously the variables E-WOM, E-TRUST and E-Service Quality Islamic have a significant and positive effect on Purchase Decision.